Diagnóstico da incidência de doenças associadas a LER/DORT em trabalhadores de câmaras frigoríficas de Curitiba e região metropolitana - Wiczick, Rodrigo Mendes (2008)
This dissertation has the purpose of diagnosing the incidence of RMI/WMSD-related illnesses in workers of freezing chambers of Curitiba and Metropolitan Area. The sample of companies taking part in the research was established considering the convenience sampling of six companies from Curitiba and RM working with freezing chambers. Five of them fully met the requirements whereas one of them fulfilled them only partially and their data were used as a reference. A questionnaire was prepared as presented below containing 34 questions involving the companies’ labor data, activity data of the research object as well as organizational data. In the study, environmental conditions experienced by the employees were studied to characterize low temperature status of the workplace, thermal sensation conditions, thermal comfort, and the subjective sensations of cold and pain. The research tools used were direct observation, inquiry and environmental parameters collection at workplace. With results obtained from field survey and softwares, the diagnosis achieved pointed to no record of RM I/WMSD-related illnesses. The complaints about pain in upper limbs are not directly connected to low temperatures; they are actually related to the rate of isolation deficiency in clothing because 90% of the interviewed workers mentioned some level of thermal discomfort.